Innovacionnye technologii optimizacii trenirovocnogo processa na osnove primenenija «umnych» vešcej, nejronnych setej i iskusstvennogo intellekta - Rostovtsev, V. L; Rostovtsev, F. V.; Kryazhev, S. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
This article discusses various ways of integrating smart technology into management of sports training plans. An insight into smart devices that utilize traditional and neural network-based software is given. Origins of the term "artificial intelligence" are discussed. Description of a simple neural net serves as an example of neural nets` capability of self-development. Differences between traditional and neural network-based software are also highlighted. Discussion of artificial intelligence`s applications in sports training process takes place. Results of applying smart technology such as programmed electromyostimulation (pEMS) yield high efficiency in physical development after a 10-day training course. Integration of artificial intelligence is proposed as a way of sports training process optimization and control.